2018
DOI: 10.1111/cmi.12835
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-ligand and parasite protein-protein interactions inPlasmodium vivax: Analysing rhoptry neck proteins 2 and 4

Abstract: Elucidating receptor-ligand and protein-protein interactions represents an attractive alternative for designing effective Plasmodium vivax control methods. This article describes the ability of P. vivax rhoptry neck proteins 2 and 4 (RON2 and RON4) to bind to human reticulocytes. Biochemical and cellular studies have shown that two PvRON2- and PvRON4-derived conserved regions specifically interact with protein receptors on reticulocytes marked by the CD71 surface transferrin receptor. Mapping each protein frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
3
11
0
2
Order By: Relevance
“…The result obtained for the cyclic peptide was different than previously reported by Vulliez Le Normand et al [15], however, to analyse these results it is important to highlight that the purity level of the peptides used in all experiments of this work were higher than 95%, (Additional file 1) that is required for reliable SPR experiments [32]. This result in agreement with the report from Bermudez et al [16] for a recombinant protein that contain a PvRON2 sequence in which the peptides studied were based.
Fig. 3Surface plasmon resonance studies of peptides based on PvRON2 (2035–2074) binding to PvAMA1-His 6 .
…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The result obtained for the cyclic peptide was different than previously reported by Vulliez Le Normand et al [15], however, to analyse these results it is important to highlight that the purity level of the peptides used in all experiments of this work were higher than 95%, (Additional file 1) that is required for reliable SPR experiments [32]. This result in agreement with the report from Bermudez et al [16] for a recombinant protein that contain a PvRON2 sequence in which the peptides studied were based.
Fig. 3Surface plasmon resonance studies of peptides based on PvRON2 (2035–2074) binding to PvAMA1-His 6 .
…”
Section: Resultssupporting
confidence: 80%
“…Therefore, it has been hypothesized that this complex is conserved in P. vivax, and this AMA1–RON2 interaction offers potential for the development of anti-infective (vaccines and/or drugs) strategies. In fact, during the development of the present study, two other works showed the interaction of peptides and recombinant proteins based on PvRON2 and PvAMA1 [15, 16].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…While the process of moving junction (MJ) formation and important players involved in the process were well elucidated in P. falciparum, the other major causative agent of malaria, P. vivax, remains poorly understood, partially owing to difficulties in culturing P. vivax in vitro. Recombinant P. vivax rhoptry neck protein 2 (PvRON2), based on literature evidence of involvement of PfRON2 in MJ formation and invasion, showed that both rhoptry proteins PvRON2 and PvRON4 bound preferentially to CD71-labeled human reticulocytes rather than normocytes [26]. More importantly, the cysteine-rich C-terminal PvRON2 region strongly interacts with PvAMA1 domains II and III, similar to earlier reports of PfRON2-PfAMA1 interactions [27].…”
Section: Invasion/egresssupporting
confidence: 80%
“…PfRON2 and PvRON2 interact with a hydrophobic groove in AMA1 [ 52 , 53 ]. It has been recently reported that PvRON2-RI (957–1288 AA) [ 52 54 ] and PvRON2-RII (1850–2085 AA) [ 54 ] bind to PvAMA1 DI [ 52 , 54 ] with high affinity [ 54 ], and in both P. falciparum and P. vivax species it was observed that the residue Tyr251, which was reported to be essential for RON2 binding [ 7 , 55 ], is conserved [ 46 , 55 ].…”
Section: Discussionmentioning
confidence: 99%